Detection of Medication Errors in Primary Care Units through Passive Voluntary Reporting Forms - Rowan W. El-Ghareeb; Nagwa Ali Sabri; Manal El Hamamsy; Amr A. Saad (Ain Shams University, 2019)
The lack of a universally accepted terminology of what constitutes a Medication Error (ME), makes it difficult to report, detect, categorize and prevent MEs. Methodologically, there isn't a complete picture of the incidence and prevalence of MEs. The broad range of ME rates in literature reflects heterogeneity in the study designs and detection methods used. The current study aimed to detect MEs in reports received from Primary Care Units. A retrospective analysis was applied on such reports dated from March to November 2013 and some fatal cases are taken from 2014. All voluntary reports were included, excluded were errors not associated with drug use and pharmaceutical company reports. Eligible reports underwent assessment using predetermined criteria to pick up MEs. The criteria were applicable on 115 reports, in which MEs were detected. 60% (69/ 115) of ME cases were error cluster while 40% (46/115) were unknown due to either underreporting, lack of data or poor observation and correlation (p< 0.05). Only 7% (8/115) p<0.001 of the reports were pregnancy cases. Moreover, errors associated with vaccine use accounted for 7% (8/115) of the cases while 93% accounted for errors from other drug use at p<0.001. Long-term follow-up was needed but not done by the assessors in 41% (47 of 115) of ME cases at p-value=0.05. Attachments were provided with the reports in 9% (10 /115) of the cases while the majority 91% (105/115) were not (p<0.001). In conclusion, voluntary reporting is a major strategy to prevent MEs by learning from errors reported.